Cognitive Behavioral Therapy: A Contemporary Approach to Treating Anxiety and Depression - Anum Iqbal; Wagma iqbal (`, 2025)
Cognitive Behavioral Therapy (CBT) stands as a preeminent, evidence based intervention for anxiety and depression, yet its contemporary landscape is marked by significant evolution and implementation challenges. This narrative review synthesizes current literature to critically examine the efficacy, adaptations, and real world application of modern CBT. The analysis confirms the robust efficacy of traditional CBT while highlighting the paradigm shift represented by third wave modalities like Acceptance and Commitment Therapy (ACT) and Mindfulness Based Cognitive Therapy (MBCT), which target Meta cognitive processes and show particular strength in preventing depressive relapse and managing chronic worry. Furthermore, digital CBT (dCBT) demonstrates comparable efficacy to face-to-face therapy for mild-to-moderate symptoms and offers a transformative solution to scalability and access barriers. The findings also reveal a growing emphasis on transdiagnostic protocols that efficiently treat underlying pathological processes common across diagnostic categories. However, significant challenges persist, including the adherence efficacy paradox in unguided digital interventions, a critical shortage of trained therapists, and the need for cultural adaptation and sustainable implementation models. The review concludes that while CBT’s therapeutic efficacy is firmly established, its future impact depends on overcoming these translational hurdles through a focus on personalized, process based care, enhanced training, and the thoughtful integration of technology within supportive, system-level frameworks. This evolution positions CBT not as a static monolith but as a dynamic and essential component of a modern mental health ecosystem. Keywords: Cognitive Behavioral Therapy, Anxiety, Depression, Third-Wave CBT, Digital Mental Health, Implementation Science, Transdiagnostic, Accessibility, Mindfulness